The investigation of the nonlocal longitudinal stress waves with modified couple stress theory - Guven, U. (SPRINGER WIEN, 2011)
In the present work, the propagation of longitudinal stress waves is investigated using a modified couple stress theory. The analysis of wave motion is based on a Love rod model including the effects of lateral deformation. The present analysis also considers the effect of shear stress components. By applying Hamilton's principle, the explicit nonlocal elasticity solution is obtained, and the effects of shear stress and length scale parameter are discussed.
Keywords: ELASTICITY; VIBRATION; Mechanics